2018
DOI: 10.15171/hpr.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Patients’ Meal Experiences through Staff’s Role: Study on Malaysian Public Hospitals

Abstract: Background: One way to improve hospital food provision is certainly by understanding the management of hospital foodservices, but there is limited detailed information about staff roles in food provision in many hospitals around the world. Objective: The hospital meal experience of patients, a part of the services provided by hospitals, is becoming important. Therefore, the role of various hospital staff members was studied through their behavior, attitudes, and practices so as to understand how the foodservic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…A previous study conducted in Malaysia indicated that the plating system (centralised or decentralised) and foodservice system (outsourcing or in-house) influence the food consumption of patients. They discovered that while the centralized plating system improved food presentation, cold food was served (16). Similarly, our findings suggest that one of the elements affecting food temperature is the type of trolley utilized during meal delivery.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…A previous study conducted in Malaysia indicated that the plating system (centralised or decentralised) and foodservice system (outsourcing or in-house) influence the food consumption of patients. They discovered that while the centralized plating system improved food presentation, cold food was served (16). Similarly, our findings suggest that one of the elements affecting food temperature is the type of trolley utilized during meal delivery.…”
Section: Discussionsupporting
confidence: 66%
“…A study using a qualitative approach by previously reported how various hospital staff (such as nurses, foodservice managers, dietitians, doctors, and ministry officials) affects patients' food consumption. They discovered that staff training and nutrition education, plating systems, and employees lacking initiative and skills were all associated with patients' food consumption (16). Another study by Vijayakumaran (2012) found that patients expected changes in various aspects of hospital food provision, whereas staff were unable to identify the factors that contributed to patients' conceptualization of hospital food, resulting in poor acceptance of hospital food (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a plausible strategy worth exploring since staff training has been linked with better service quality [ 46 ]. Understanding hospital foodservice management is one of the strategies to enhance hospital food provision [ 47 ]. A few studies focused on strategies such as the inclusion of room service [ 30 , 31 , 32 , 33 , 34 ], menu modifications [ 29 ], meal-serving style [ 36 ], menu presentation [ 35 ], and the dietary intake monitoring tool [ 28 ], but none of the studies intervened in staff training.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, two studies that were conducted in Malaysia [ 47 , 48 ] emphasized hospital personnel’s role in food provision and investigate staff attitudes and behaviors during patients’ mealtimes. The viewpoints and experiences of important stakeholders aided in the development of knowledge in several aspects of hospital meal production that affect patients’ decisions to accept and eat food.…”
Section: Discussionmentioning
confidence: 99%